Migrant workers in a corner of the growth triangle - Ace Partadireja (Economic Journal of Emerging Markets, 1995)
Twenty kilometers southest of Singapore or about 25 minutes by ferry, there is an Indonesian Island, Batam. This 415 sq km island, with reddish yellow podzolic soil, is agriculturally good for nothing but tropical schrubs, snakes and monkeys, and some would add, is financcially a loss to the Indonesian government.